EFEKTIVITAS PENGGUNAAN MEDIA GAMBAR KOMIK TERHADAP HASIL BELAJAR BAHASA ARAB PESERTA DIDIK KELAS VII MTS DDI SABANG KABUPATEN TOLITOLI - Nia Ramadani; Jafar Sidik; Zul Aini Rengur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of comic picture media on the Arabic language learning outcomes of seventh-grade students at MTs DDI Sabang, Tolitoli Regency. The background of this research is the low learning outcomes of students, which only reached an average score of 67.50, far below the minimum completeness criteria set at 75, due to the dominance of lecture methods without adequate learning media support. This study employed a quantitative approach with a pre-experimental type using a one group pretest-posttest design. The research subjects were all seventh-grade students of MTs DDI Sabang totaling 22 students using a saturated sampling technique. Data were collected through a 20-item multiple choice test and analyzed using the Shapiro-Wilk normality test, Levene Test for homogeneity, and paired sample t-test hypothesis testing through IBM SPSS 26.0. The results showed an increase in the average score from 67.50 on the pretest to 82.64 on the posttest. The paired sample t-test produced a significance value of 0.000, meaning the alternative hypothesis was accepted. It is concluded that the use of comic picture media is effective in improving Arabic language learning outcomes of seventh-grade students at MTs DDI Sabang, Tolitoli Regency, and contributes to the realization of quality education in accordance with SDGs Goal 4.